USE AND EFFICIENCY OF GEOTEXTILE MATERIALS IN ROAD CONSTRUCTION - Ashurov Elyor Tulkinovich (International Engineering Journal For Research & Development, 2021)
In this article, the use of geotextile materials in the construction and repair of roads is growing. The strength of the geotextile material is high, the air is full, and the water is easily permeable. Geotextiles are widely used in road and hydraulic structures, transport and engineering communications.